The ability of Mycophenolate Mofetil to induce chromosome aberration and DNA damage in Mus Musculus Mice - RUIDA WATHEQ NEAMA; WAJDI SABEEH SADEQ (Tikrit Journal of Pure Science)
Mycophenolate mofetil (MMF, cellcept) is widely used in maintenance immunosuppressive therapy for prevention refractory rejection in sold organ transplant recipients. MMF is orally used, and rapidly metabolized to its active constituent Mycophenolic acid. MPA is an inhibitor of Inosine Monophosphate Dehydrogenase ΙΙ (IMPDH ΙΙ) in lymphocyte causing in reduction in intracellular guanine nucleotide pools and leads to inhibition of lymphocyte proliferation. MMF is considered to be an effective and safe immunosuppressive agent compared with other medicins. MMF lacks the nephrotoxicity. But it has important side effects, gastrointestinal and heamatological adverse effects are the most common. The results of this study show the high significant in total chromosome aberrations in treatment groups compared with control. Also there is high significant differences in total damage DNA in treatment groups than control. In conclusion, MMF may has a high genotoxicity by induced chromosome aberration and DNA damage.